Structural implications for K5/K12-di-acetylated histone H4 recognition by the second bromodomain of BRD2 - Umehara, Takashi (2010)
The BET family proteins recognize acetylated chromatin through their two bromodomains, acting as transcriptional activators or tethering viral genomes to the mitotic chromosomes of their host. The structural mechanism for how the N-terminal bromodomain of human BRD2 (BRD2-BD1) deciphers the mono-acetylated status of histone H4 tail was recently reported. Here we show the crystal structure of the second bromodomain of BRD2 (BRD2-BD2) in complex with the di-acetylated histone H4 tail (H4K5ac/K12ac). To our surprise, a single K5ac/K12ac peptide interacts with two BRD2-BD2 molecules simultaneously: the K5ac residue binds to one BRD2-BD2 molecule while the K12ac residue binds to another. These results provide a structural basis for the recognition of two different patterns of the histone acetylation status by a single bromodomain. STRUCTURED SUMMARY: MINT-7989882, MINT-7989824, MINT-7989846, MINT-7989865: H4 (uniprotkb:P62805) binds (MI:0407) to BRD2 (uniprotkb:P25440) by surface plasmon resonance (MI:0107) MINT-7989539: H4 (uniprotkb:P62805) and BRD2 (uniprotkb:P25440) bind (MI:0407) by X-ray crystallography (MI:0114)